Desenvolvimento Territorial e Turismo Rural: As relações possíveis - Silvana Kloster (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2014)
The article discusses the formation of rural land and the changes occurring in rural Brazil from addressing the duality of the agrarian system to the new conceptions of local development projects involving non-agricultural activities such as rural tourism. It is a discussion of territorial tourism, which is an agent capable of modifying the territory using endogenous elements, may cause different impacts and / or risks to agricultural territories. The minimization of the negative impacts is the great challenge studied by different areas of knowledge.